Expressivism and the practicality of moral convictions - Sinclair, Neil (Springer, 2007)
Many expressivists have employed a claim about the practicality of morality in support of their view that moral convictions are not purely descriptive mental states. In this paper I argue that all extant arguments of this form fail. I distinguish six versions of such arguments and argue that in each case either the sense of practicality the argument employs is too weak, in which case there is no reason to think that descriptive states cannot be practical or the sense of practicality the argument employs is too strong, in which case there is no reason to think moral convictions are practical. I also discuss and dismiss an attempted patch of such arguments provided by Humean Psychology. The conclusion is that expressivists need to look to sources other than the alleged practicality of morality to support their position. In concluding remarks I suggest one such alternative.